A Tool to Measure Livelihood Vulnerability of Climate-Sensitive Farming Communities - Kumar Hebsale Mallappa, Vinaya; Gadde, Sriharsha (Indian Journal of Extension Education, 2025)
Climate change is one of the major concerns for rural livelihoods, particularly for families dependent on agriculture. Understanding livelihood vulnerability to climate change is essential for developing adaptive strategies. The present study, conducted in March 2025, aimed to develop a scale for livelihood vulnerability by incorporating three dimensions: exposure, sensitivity, and adaptive capacity. From an initial pool of 53 statements, 36 were finalized after expert validation and statistical screening. The Likert methodology was used to assess the statements. Content validity was established through expert review, and internal consistency of the scale was assessed by using Cronbach’s alpha (0.90), indicating high reliability. The final scale offers a comprehensive, reliable tool for assessing livelihood vulnerability to climate change and can be used for research, policy formulation, and relevant interventions in climate-sensitive regions.
Keywords: Livelihood vulnerability; Climate change; IPCC framework; Adaptive capacity; Sensitivity; Exposure